Managing anxiety disorders with the neuro-biofeedback method of Brain Boy Universal Professional - Eleftheria Zafeiri; Vasileios Dedes; Kostantinos Tzirogiannis; Agapi Kandylaki; Maria Polikandrioti; Dimitris Panidis; Georgios I. Panoutsopoulos (Health Psychology Research)
# Background